Constructing and deconstructing the Gokstad mound. (October 2020) - Cannell, Rebecca J.S.; Bill, Jan; Macphail, Richard
Abstract: Abstract : Viking Age burial mounds are usually interpreted with reference to their exterior dimensions, the funerary treatment of the deceased and the artefacts placed within them. The process of constructing these mounds, however, may also have played an important role in funerary traditions. Investigations at the Gokstad mound in Norway demonstrate that the building of this mound—in terms of its phases and material expressions—formed an integral part of the overall burial rite. The complex construction sequence contained references to both the physical and mythical landscapes, revealing the potential of the study of burial mound construction at other sites in Viking Age Scandinavia and beyond.